Preliminary Survey for Spiders on Antigua, West Indies - Sewlal, Jo-Anne Nina (International Journal of Bahamian Studies, 2009)
Spiders have a worldwide distribution that comprises all land environments except at the polar extremes. There are now 40,700 named, described species of spiders (Platnick, 2009), thought to represent about one-fifth of the true total. On a faunistic level, the spiders of some regions are reasonably well known, but this is far from the case in the New World tropics, including the West Indies. At present, we have species-level surveys for Cuba (Alayón, 1995), Barbados (Bryant, 1923; Alayón & Horrocks, 2004), St. Vincent & the Grenadines (Simon, 1894; de Silva, Horrocks & Alayón, 2006), Anguilla (Sewlal & Starr, 2006), Nevis (Sewlal & Starr, 2007), St. Kitts (Sewlal, 2008) and Grenada (Sewlal, 2009a), and a family-level list for Trinidad (Cutler, 2005, Sewlal & Cutler, 2003, Sewlal & Alayón, 2007, Sewlal, 2009b). Additional information on the family Pholcidae of some of the Lesser Antilles is provided by Sewlal and Starr (2008). The present short communication serves to expand on Bryant’s (1923) list of 23 species from Antigua and to treat the species distribution on the island with respect to habitats. This survey adds 18 species and 11 families to the list compiled by Bryant (1923).